Sustainable Human Development Across the Life Course Evidence from Longitudinal Research - Banati, Prerna (Bristol University Press, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC licence. It is critical that the wellbeing of society is systematically tracked by indicators that not only give an accurate picture of human life today, but also provide a window into the future for all of us. This important book presents impactful findings from twelve international longitudinal studies that responded to the Agenda 2030 commitment to "leave no-one behind". Exploring a wide range and complexity of global issues, it provides actionable strategies for policy makers and practitioners to strengthen the global Sustainable Development Goals framework and accelerate their implementation."